The Role of Neutrophil Extracellular Traps in Cancer - Shao, Bo-Zong; Yao, Yi; Li, Jin-Ping; Chai, Ning-Li; Linghu, En-Qiang (Frontiers in Oncology, 2021)
Neutrophils are vital components of innate and adaptive immunity. It is widely acknowledged that in various pathological conditions, neutrophils are activated and release condensed DNA strands, triggering the formation of neutrophil extracellular traps (NETs). NETs have been shown to be effective in fighting against microbial infections and modulating the pathogenesis and progression of diseases, including malignant tumors. This review describes the current knowledge on the biological characteristics of NETs. Additionally, the mechanisms of NETs in cancer are discussed, including the involvement of signaling pathways and the crosstalk between other cancer-related mechanisms, including inflammasomes and autophagy. Finally, based on previous and current studies, the roles of NET formation and the potential therapeutic targets and strategies related to NETs in several well-studied types of cancers, including breast, lung, colorectal, pancreatic, blood, neurological, and cutaneous cancers are separately reviewed and discussed.